EFEKTIVITAS BAKTERI ENDOFIT SEBAGAI PUPUK HAYATI TERHADAP PERTUMBUHAN DAN PRODUKSI CABAI (Capsicum annuum, L.) - Rahmi Zuhra (Talenta Publisher, 2017)
The endophytic bacteria is one of the microbes that can be used as a biofertilizer to enhancethe growth and production of chili. The aim of research to determine the effectivity ofendophytic bacteria as biofertilizer origin of chili and corn to increase the growth andproduction of chili. The experiment was conducted at home of gauze, Langsa Aceh. Theresearch method is a randomized block design with 19 treatment and 3 replication. Theresults showed that isolates A1 (from roots chili) and A20 (from the roots of corn) wereeffective against root growth, while the A24 isolates (from corn stalks) are effective againstplant height and chili.